Minimally Invasive Approaches in Pediatric Dentistry - Sarah Mohammed Khammas; Hamsa Thabet Musa; Saja Sami Malik; Samara Faris Abdulazeez; Asmaa Mohammed Khammas; Shatha Abdullah Abbas (Dentistry 3000)
The aim of this work was to assess the efficacy, affordability, and acceptability of various “non-invasive and minimally invasive techniques” that are used in treatment of carious lesion in children. Minimally invasive techniques represent a paradigm shift in pediatric dentistry, emphasizing patient-centered care and preserving healthy tooth structure. Considering continuing technological development these techniques will become even more crucial in providing safe, effective, and comfortable dental experiences for children allowing pediatric dentists to foster a positive and e stress-free environment for children, establishing the foundation for long-term dental health.